Prospect of Sustainability Course for Student’s Engagement in ESD - Ferdous Ahmed; Muhammad Rehan Dastagir; Mohammed Ataur Rahman; Selina Nargis (Journal of Sustainability Perspectives, 2021)
Educating and preparing young graduates with an actionoriented education program is the prime requirement for any country. Therefore, the Sustainability course is designed to develop resource persons to fulfill the immediate country’s demand for adequate ESD (Education for Sustainable Development) skilled graduates. Currently Bangladesh is thriving for Sustainable Development Goals (SDGs) by implementing the sustainability practices into the educational institutions. However, IUBAT is the pioneer for setting the sustainability course in undergraduate studies for any disciplines. Since today more than 10,000 undergrad students of the different disciplines have been taught the sustainability course where they engaged and practiced for any environmental degradation and resource conservation. Moreover, these students also spreading their sustainability knowledge and practices going to secondary and higher secondary school and colleges as a part of course assignments. Meanwhile IUBAT is a Green Campus, therefore students can practice for ESD with the appropriate green facilities. The aim of this paper is to disseminate the knowledge sharing that IUBAT leads introducing sustainability education at undergraduate level. This also highlights how IUBAT students are dedicated to participate and practicing for sustainable education for their lifelong learning which ultimately supports a nation’s dream of achieving SDGs by 2030.